2016
DOI: 10.1097/rct.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Cartilage Thickness and Meniscus Extrusion Predict Longitudinal Cartilage Loss by Quantitative Magnetic Resonance Imaging

Abstract: Objective To assess how meniscus damage and baseline cartilage thickness influence the rate of cartilage loss and knee pain. Methods Of 4,796 participants in the Osteoarthritis Initiative (OAI), 86 had baseline and 48 month follow-up quantitative MRI data for medial compartment cartilage thickness. Baseline meniscus pathology was scored by a musculoskeletal radiologist using Whole-Organ Magnetic Resonance Imaging Score (WORMS). Findings were correlated with 72-month Knee Injury and Osteoarthritis Outcome Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A previous study showed that subjectively graded joint space narrowing was a risk factor for frequent pain in subjects that had frequent knee pain in one knee but not in the contralateral knee [ 9 ]. However, other investigators have not been able to document an association between joint space narrowing and symptoms [ 10 - 11 ]. A re-analysis of the data using the threshold limit graphical approach described in this paper may provide additional insights into the association between change in the knee joint space and outcomes in the OAI study, other knee studies, and eventually in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that subjectively graded joint space narrowing was a risk factor for frequent pain in subjects that had frequent knee pain in one knee but not in the contralateral knee [ 9 ]. However, other investigators have not been able to document an association between joint space narrowing and symptoms [ 10 - 11 ]. A re-analysis of the data using the threshold limit graphical approach described in this paper may provide additional insights into the association between change in the knee joint space and outcomes in the OAI study, other knee studies, and eventually in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal medial tibiofemoral compartment cartilage structural progression over 8 years was associated with worsening semiquantitative meniscal tear scoring for the combined medial and lateral menisci over 8 years 26 . Only two of the 16 cohort analyses did not support the association of meniscal tear with structural progression 25,38 .…”
Section: Osteoarthritis and Cartilagementioning
confidence: 92%
“…While walking speed decline is a prognostic marker of knee OA, how it relates to structural changes prior to the onset of radiographic OA remains unclear. Understanding whether early changes in walking speed are associated with commonly used sensitive measures of knee health that are related to OA onset and progression (e.g., changes in bone marrow lesions [BMLs; ], effusion , or cartilage ) may provide a better understanding of the early link to physical function and joint health decline.
Understanding whether early changes in walking speed are associated with sensitive measures of knee structure may provide a better understanding of the early link to physical function and joint health decline. Individuals with accelerated knee osteoarthritis present with earlier worsening of knee structure as well as poorer patient‐reported and physical function measures compared to individuals with a more common, gradual onset of knee osteoarthritis. Individuals with accelerated knee osteoarthritis who slowed their walking speed were 3.0 and 3.4 times more likely to demonstrate an increase in bone marrow lesion and effusion volume, respectively. Cartilage structure changes were not associated with walking speed decline in individuals with accelerated or common knee osteoarthritis.
…”
Section: Introductionmentioning
confidence: 99%